Online Media Literacy Of Culinary Msmes To Increase Sales During The Pandemic And After Covid-19 - Ervani, Eva; Indrawati, Dini; Hayati, Amelia; Karsinah, Karsinah (Indonesian Journal of Devotion and Empowerment, 2024)
This PPM activity aimed to provide literacy through socialization and direction regarding the use of various online media to culinary MSME actors in the district and city of Bandung, West Java in an effort to increase product sales in the midst of the Covid-19 pandemic and during the recovery period from pandemic conditions. The decline in economic levels in various sectors was one of the most serious impacts of the COVID-19 pandemic, as experienced by culinary MSME entrepreneurs in Indonesia, including culinary MSME entrepreneurs in the district and city of Bandung. The decline in sales levels for culinary MSME business actors had resulted in a decline in income and welfare levels. The presence of online media as a technology that could help and facilitate culinary MSME business actors as a strategy to carry out promotions with the aim of increasing sales in the midst and the recovery period of the Covid-19 pandemic. The method in this PPM activity was through literacy for culinary MSMEs through socialization activities, briefings, and sharing pamphlets. This PPM activity was expected to produce output to provide solutions for culinary MSME actors to be able to increase sales of their products through the use of online media in the midst and the recovery period of the Covid-19 pandemic. From this PPM activity, it is suggested that culinary MSMEs be more active in participating in activities such as workshops or training to improve their ability to do business digitally or online.